The Research Progress of Exosomes in Osteoarthritis, With Particular Emphasis on the Therapeutic Effect - Xian Bo, Shang; Chen, Wang; Chang, Liu; Hao Ran, Yu; Hui Hui, Guo; Ya Kun, Zhu; Wu Kun, Xie; Hai Tao, Fan; Wen Dan, Cheng (Frontiers in Pharmacology, 2022)
Exosomes participate in many physiological and pathological processes by regulating cell-to-cell communication, which affects the occurrence and development of diseases such as osteoarthritis (OA). While exosomes in the microenvironment of OA tissues are involved in the pathological progression of OA, exosomes derived from therapeutic cells have the potential to become a new therapeutic strategy for OA. The latest research has shown that exosomes participate in OA treatment by regulating the proliferation, apoptosis, inflammation, and extracellular matrix synthesis of chondrocytes in OA. However, studies in this field are few. This review summarizes the therapeutic effect of exosomes on chondrocytes in OA and their molecular mechanisms. We also discuss the challenges and prospects of OA treatment based on exosomes.